2013
DOI: 10.1128/jcm.00251-13
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Trans-Vag Broth, Colistin-Nalidixic Agar, and CHROMagar StrepB for Detection of Group B Streptococcus in Vaginal and Rectal Swabs from Pregnant Women in South Africa

Abstract: d Maternal vaginal colonization with group B streptococcus (GBS) is a major risk factor for invasive GBS infection in newborns.The CDC-recommended method for detecting GBS colonization is to culture vaginal and rectal swabs in a selective broth followed by subculture on blood agar or a selective medium. A high incidence of antimicrobial resistance in the fecal microflora can compromise the recovery of GBS from the selective broth. Here, we compared CHROMagar StrepB (CA), Columbia colistinnalidixic agar (CNA), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 27 publications
3
11
0
Order By: Relevance
“…Comparison of SBA, CNA and SCB methods revealed that SCB was the most reliable. The sensitivity of CNA was similar to previous reports [ 6 , 9 ] as was the sensitivity of SCB [ 3 ]. SCB is more expensive than SBA or CNA but processing time is reduced.…”
Section: Discussionsupporting
confidence: 90%
“…Comparison of SBA, CNA and SCB methods revealed that SCB was the most reliable. The sensitivity of CNA was similar to previous reports [ 6 , 9 ] as was the sensitivity of SCB [ 3 ]. SCB is more expensive than SBA or CNA but processing time is reduced.…”
Section: Discussionsupporting
confidence: 90%
“…Our study has several limitations. First, our results are limited by the sensitivity of detection of GBS on selective media, estimated at 85% 30 and by the fact that we identified the serotype by conventional PCR. This may imply that we have underestimated low levels of colonisation in infants where DNA was below the limit of detection.…”
Section: Discussionmentioning
confidence: 87%
“…We tried to optimize the comparability of our assay to that of other laboratories by calibrating our in-house reference (Polygam) with reference sera from C. J. Baker, who has published widely in the field. Secondly, the sensitivity of detection of GBS on selective media is estimated at 85% and mainly identifies the dominant colonizing serotype, with lower-density co-colonizing serotypes likely being missed [23]. Therefore, it is possible that we overestimated new acquisition through missing colonization episodes not detectable by standard culture methods at visit 1, and we similarly may also have missed some new acquisitions.…”
Section: Discussionmentioning
confidence: 93%
“…Samples were collected by trained study nurses with rayon-tipped swabs that were placed into Amies transport medium without charcoal (Transwab Amies; Medical Wire, UK). For GBS isolation, swabs were inoculated onto CHROMagar StrepB (CA; Media Mage, South Africa) as previously described [23]. Serotyping was performed by the latex agglutination method with specific antisera (Statens Serum Institute, Sweden) to serotypes Ia, Ib and II to IX CPS antigens, as previously described [24].…”
Section: Study Populationmentioning
confidence: 99%